Detection of Open-Circuit Faults in Multi-Level Hybrid Active Neutral Point Clamped Inverters - Halabi, Laith M.; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (Journal of Electrical Engineering and Technology, 2022)
In the field of renewable energy, power converters serve an important role in power generation systems. However, they are vulnerable to faults of several types, among which open-circuit faults are the most common. In this context, this paper proposes an efficient method to detect and identify faults in various components of power converters accurately. The distortion in the output voltage and current waveforms of the system induced by open-circuit faults are calculated and compared to pre-established threshold values to detect the faulty devices. In addition, an accurate look-up table is prepared to identify locations of faults in multi-level inverters. The proposed method is analyzed in detail and its effectiveness is verified based on simulation and experimental results. The results demonstrate that the proposed method improves fault detection significantly.
Keywords: Active neutral point clamped; Current distortion; Faults detection; HANPC; Multi-level inverter; Multilevels; Neutral-point clamped inverters; Open-circuit fault; Open-circuits; Renewable energy power; Current distortion; Fault detection; HANPC; Multi-level inverters; Open-circuit